Age-sex differences in Alzheimer’s and related dementias burden and risk factors in east and Southeast Asia: results from the 2021 GBD study - Tengyu Zhao; Pengyu Pan; Yuhan Zhou; Xinyue Zhang; Quan Li; Yanyan Zhou; Yanyan Zhou (Frontiers in Aging Neuroscience)
BackgroundAlzheimer’s disease and related dementias (ADRD) significant global public health challenges, leading to severe disability in patients and placing a heavy burden on caregivers. However, epidemiological studies focusing on ADRD in specific regions remain limited. This study aims to comprehensively analyze and describe the current status and changing trends of ADRD in Non-High-income East Asia (NHIEA), Non-High-income Southeast Asia (NHISEA), and High-income Asia Pacific (HIAP), providing more detailed real-world data to inform policymaking.MethodsThe data for ADRD used in this study were extracted from the 2021 Global Burden of Disease (GBD) database. We employed three major indicators of disease burden—prevalence, incidence, and years lived with disability (YLD)—and explored associated risk factors, further analyzing trends by age and sex. The results are presented as mean values with 95% uncertainty intervals (UIs). Additionally, we explored the differences between NHIEA, NHISEA, HIAP and other regions, as well as the potential associations between the disease burden of Alzheimer’s and other dementias and socioeconomic factors.ResultsThe findings indicate that the burden of dementia is rising in East and Southeast Asia, with women showing a higher burden across all indicators. Notably, in NHIEA, particularly in China, the burden of dementia has increased with the rising Social Demographic Index (SDI). China experienced a 27.3% increase in Alzheimer’s disease and other dementia ASYRs from 1990 to 2021, with a sharp 7.6% annual surge in 2021 alone, outpacing regional averages. Gender analysis revealed that women bear a disproportionate burden of Alzheimer’s disease and related dementias, especially after menopause, when the risk increases significantly. The study also identified smoking, high blood sugar, and high body mass index as important risk factors affecting the disease burden. The contribution of these risk factors varies across regions, genders, and age groups.ConclusionThe health burden of ADRD remains substantial, with distinct patterns observed across NHIEA, NHISEA, and HIAP, including regional variations in gender, age, and risk factors. These findings highlight the need for tailored approaches to allocate healthcare resources and implement appropriate control measures based on the specific conditions of each region to address this growing public health challenge. Future research should prioritize comparative analyses across continents and within regions to inform the development of more region-specific prevention strategies for ADRD.